The ability to punch in the front for students of pencak silat uns achievement (Correlational Study Viewed from Eye-Hand Coordination, Arm Length and Arm Power) - Ulum Muhammad Bahrul; Kristiyanto Agus; Slamet Riyadi (H.S. Skovoroda Kharkiv National Pedagogical University, 2020)
The aim  of this study was to determine the interaction of eye-hand coordination, arm length and arm power with the ability to punch in front of the students of UNS Pencak Silat achievement coaching. Material and methods. The design or research design used is to use descriptive methods with correlational study techniques (correlation design). This research will describe the relationship and the amount of contribution between eye-hand coordination, arm length and arm power with the ability to punch ahead in the Pencak Silat sport. The population in this study were all students of UNS pencak silat achievement coaching which included fostering the achievements of the Faculty of sport, Tapak Suci student activity units, PSHT student activity units, Merpati Putih student activity units and student self-defense units. Results. Based on the results of research and the results of data analysis that has been done, the following conclusions can be obtained: There is a significant relationship between eye-hand coordination, arm length and arm power with the ability to punch in front of pencak silat with a significant value F count = 64,99 > F table = 2,81. Conclusions.  Contribution of eye-hand coordination is the variable that has the most dominant contribution, then followed by the arm power variable and the smallest contribution is the arm length variable. Meanwhile the remaining 19.1% is contributed by factors other than those represented by independent variables. Predictions from researchers of these other factors could have been influenced by training factors or other physical condition factors that also supported the ability to punch in front of pencak silat.